Persisting Short or Long Sleep Duration Predicts Post-Stroke Depression One year After Stroke and Transient Ischemic Attack - Hu Y; Zuo L; Pan Y; Yan H; Wang Y; Zhao X (Nature and Science of Sleep)
Yang Hu,1,* Lijun Zuo,1,* Yuesong Pan,2 Hongyi Yan,2 Yongjun Wang,1 Xingquan Zhao1 1Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2National Clinical Research Center for Neurological Diseases, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xingquan Zhao, Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, No. 119, South Fourth Ring West Road, Fengtai District, Beijing, People’s Republic of China, 100070, Tel +0086-010-59978350, Fax +0086-010-59973383, Email zxq@vip.163.comObjective: Disrupted sleep duration is associated with the risk of stroke, and abnormal sleep duration predicts depression. However, the association of changes in sleep duration with functional outcome and depression after acute ischemic stroke (AIS) or transient ischemic attack (TIA) is still unclear.Methods: All patients diagnosed with AIS or TIA in the impairment of cognition and sleep (ICONS) from the China National Stroke Registry III were included. Post-stroke depression (PSD) was defined as a value on the Patient Health Questionnaire-9 (PHQ-9) ≥ 5. Sleep duration was classified as normal (7– 8 hours), short (< 7 hours), or long (≥ 9 hours). According to the sleep duration, patients were divided into four groups: group A (persisting normal), group B (changed from long or short to normal), group C (changed from normal to long or short), and group D (persisting long or short). Logistic regression was performed to evaluate the effects of sleep duration changes on PSD, quality of life, and functional outcome at 1-year follow-ups.Results: A total of 1450 AIS or TIA patients at baseline with a mean age of 60.73± 10.82 years were followed for 1-year. The group with persisting long or short sleep duration exhibited a significantly higher risk of PSD [OR 1.58(95% CI (1.06~2.33)] and poor quality of life [OR 1.42(95% CI 1.04~1.94)] than those in the persisting normal group at 1-year after AIS and TIA when adjusted for covariates. Patients with a decreased sleep duration of > 1 hour had more risk of moderate to severe PSD [OR 2.26(95% CI 1.13~4.53)] than the persisting normal group. Patients with newly developed abnormal sleep duration (changed from normal to long or short) had a higher risk of poor functional outcome [OR 2.82(95% CI 1.33~5.96)] than the persisting normal group.Conclusion: The alterations in sleep duration were independently associated with PSD, poor quality of life, and adverse outcomes at 1-year, suggesting that inadequate sleep quantity plays an important role in 1-year depression, quality of life, and adverse outcomes after AIS or TIA.Keywords: mild stroke, persisting cognitive impairment, Montreal cognitive assessment-Beijing, functional dependence